الدليل المستمد من إجراء باطل: دراسة تأصيلية تطبيقية على نظرية البطلان ونظام الإجراءات الجزائية السعودي - الزهراني، رجب بن فارس بن رجب (جامعة الأزهر - كلية الشريعة والقانون بدمنهور, 2024)
إحداث التوازن بين المصلحة العامة للمجتمع والمصالح الفردية في صياغة القواعد القانونية، مهمة المبادئ القانونية العامة، ومن ذلك التوازن بين " مبدأ حق الدولة في العقاب والتجريم " و" مبدأ الشرعية الإجرائية الجزائية " الذي حرص على حماية حقوق الأفراد والحريات العامة، حيث لا جريمة ولا عقوبة إلا بنص، ولذا فإن بحث آثار مخالفة مبدأ الشرعية الإجرائية، ودراسة الجزاء القانوني للمخالفة مهم، ومن ذلك دراسة " الأدلة المستمدة من إجراءات باطلة"، وهل يمكن استبعاد الدليل من عدمه، مع عدم إغفال تحقق الغاية منه، وهي قاعدة مقررة في بعض التشريعات المقارنة، إلا أن تطبيقها في التشريعات العربية ومنها النظام السعودي، لا يمكن اعتباره قاعدة مطردة، ومع ذلك يلاحظ استدعاء نظرية البطلان في نظام الإجراءات الجزائية السعودي والتفريق بين الإجراءات الباطلة بطلانا نسبياً وبطلانا مطلقاً، وأثر ذلك على الدليل المستمد من هذا الإجراء الباطل، ويمكن التقعيد للقاعدة في الشريعة الإسلامية، عن طريق النظر في كلام الفقهاء باستبعاد الفقهاء اتفاقاً، الإقرار كدليل وبينة إذا صدر عن إكراه في حالة الزنا، وأنه لا يترتب عليه الحد إطلاقاً. Striking a balance between the general interest of society and individual interests in formulating legal rules is the task of general legal principles, including the balance between the "principle of the state's right to punish and criminalize" and the "principle of criminal procedural legitimacy," which was keen to protect the rights of individuals and public freedoms, where neither crime nor A punishment other than a provision, and therefore, examining the effects of violating the principle of procedural legality, and studying the legal penalty for the violation, is important, including studying "evidence derived from invalid procedures," and whether or not the evidence can be excluded. Without forgetting to achieve its purpose, it is a rule established in some comparative legislation, but its application in Arab legislation, including the Saudi system, cannot be considered a consistent rule. However, it is noted that the theory of invalidity is invoked in the Saudi criminal procedure law and the distinction between invalid procedures is relative invalidity and absolute invalidity. And the impact of this on the evidence derived from this invalid procedure, and it is possible to follow the rule in Islamic law, by looking at the words of the jurists that the jurists ruled out, in agreement, the acknowledgment as evidence and evidence if it was issued by coercion in the case of adultery, and that it does not entail punishment at all.
Keywords: الشريعة الإسلامية -- الإجراءات الجزائية -- نظرية البطلان -- القواعد القانونية -- حقوق الإنسان